Integrating local knowledge when mediating learning of food preservation in a Namibian multicultural Grade 6 class - Shetunyenga, Shetunyenga Fillipus (Rhodes University, Faculty of Education, Department of Education, 2020)
The challenge posed by multicultural classrooms has been acknowledged in many studies. Some scholars believe that the knowledge learners bring to school from their homes or community forms a basis for the knowledge to be acquired at school. That is, if learners' cultural experiences and/or indigenous knowledge are integrated into teaching of science, learners might make good sense of science. Even though the Namibian National Curriculum has responded well to the calls of recognising and integrating indigeno us knowledge during teaching and learning, it has failed to provide guidance on how this should be done. Therefore, there is a need to minimise the gap between the intention of the National Curriculum and the implementation of this intended curriculum at classroom level. It is against this background that this study sought to investigate whether or not learners' conceptions and attitudes are influenced by integrating local or indigenous knowledge when teaching food preservation in a Namibian multicultural classroom context. Underpinned by an interpretive paradigm, the study took the form of a mixed-method case study approach. It was conducted at an urban combined school in the Oshana region, Namibia. The sample consisted of 29 Grade 6 learners doing Agricultural Science, the grade 6 Agricultural Science teacher and four community members from different cultural groups. The community members were invited to demonstrate how they culturally preserve mahangu (wheat), fish, milk, and meat in their respective cultures. Data were generated using the pre-and post-intervention questionnaires, a group activity, observations (videotaped lessons) and learners' journal reflections. Quantitative data from the pre- and post-intervention questionnaires were analysed deductively and presented in tables and graphs. On the other hand, a thematic approach was used to inductively analyse qualitative data, where Vygotsky's (1978) socio-cultural theory was used as a theoretical lens focusing on culture, mediation, and social interactions. The findings of this study revealed that learners' conceptions, attitudes, and interest shifted positively as a result of the integration of local or indigenous knowledge on food preservation. Additionally, during the presentations by the community members, learners were actively engaged, asking questions and showing interest in learning about other cultures. The study thus recommends that Agricultural Science or science teachers should, where possible, make efforts to integrate local or indigenous knowledge in their multicultural classrooms.
Keywords: Food -- Preservation -- Study and teaching (Elementary) -- Namibia; Ethnoscience -- Study and teaching (Elementary) -- Namibia; Ethnoscience -- Namibia; Education, Elementary -- Namibia; Multicultural education -- Namibia